EVALUATION OF COSTS OF SERVICE AND REPAIR OF CARS IN THE POLISH MAIL COMPANY - Droździel, Paweł; Siłuch, Dariusz (Doprava a spoje, 2011)
Economic effectiveness of car use in a transport company is one of the many measures used in the evaluation of transportation services. It is influenced by many diverse factors, which include the technical condition of the means of transport, intensity of vehicle use, transport rates, costs of maintenance materials, personnel costs and costs of repairs and services, as well as taxes and administration fees. A detailed analysis of the effect of the individual factors on the level of profit gained from transport services allows evaluation of the economic effectiveness of a given transport company. The costs of vehicle repairs are one of the factors that influence the profit gained from transportation services. The present paper discusses the results of statistical analyses of data concerning the costs of repair of delivery trucks used by the Polish Mail company in Lublin.